Barriers to screening and diagnosis of peripheral artery disease by general practitioners. (December 2013) - Haigh, Kate Jamilla; Bingley, John; Golledge, Jonathan; Walker, Philip J
Peripheral artery disease (PAD) is a strong predictor of cardiovascular morbidity and mortality yet it is under-recognised and undertreated. General practitioners (GPs) are best positioned to detect patients with PAD. This article investigates awareness of PAD by GPs; the prevalence of screening for PAD and tools used for screening and diagnosis, in particular the ankle–brachial index (ABI); and the barriers to PAD screening and measurement of the ABI in the general practice setting. A cross-sectional survey of primary care practitioners was conducted between September 2011 and March 2012. A mail-out survey was distributed to 1120 GPs practising in Queensland, Australia: 287 (26%) responded; 61% of GPs reported screening for PAD; 58% of GPs reported 'never' measuring the ABI; and 70% reported using arterial duplex ultrasound as their first-line diagnostic tool. Equipment availability, time constraints and lack of training and skills were identified as the most significant barriers to screening and ABI testing. In conclusion, there are deficits in the utilisation of guideline recommendations relating to PAD screening and diagnosis by Australian GPs. Our data suggest that earlier detection of PAD may be achieved through GP education combined with increased access to ABI equipment or the availability of a more time-efficient test.